BERBAGAI KEBIJAKAN UMKM CAFFEIN DALAM MENINGKATKAN PRODUKTIVITAS, EFISIENSI DAN PENDAPATANNYA - Haryanto, Hery; Chyntia, Chyntia; Novia, Jessica; Willyanto, Lia; Sisca, Veni (Faculty of economcs Universitas Singaperbangsa Karawang, 2022)
The policies of a company or industry are needed to increase productivity, efficiency, and income. The purpose of this study was to determine the policies used by an MSME in Dumai named Caffein. In addition, to help find solutions to existing problems from each policy that has been made. This data collection technique was carried out by interviewing the owners of Caffeine MSMEs. The policy made by MSME owners at the beginning of the covid-19 hit was to reduce employees and reduce tools and materials. When covid-19 began to subside, Caffeine customers increased. Caffeine's situation is understaffed and causes the service to be out of control. From each policy that is determined, there are still problems that make the Caffeine MSME owners have to change their policies again. This study shows that each policy made by the owner of MSMEs has its own impact.